Hypoglycemia associated with fluoroquinolone: a pharmacovigilance analysis from 2014 to 2023 based on the FDA adverse event reporting system - Dan Li; Yuan Zhang; Yu Qi Wang; Lei Cheng; Xiao Dan Zhou; Jia Chen; Guo Wen Feng; Ya Ling Chen; Yun Chen; Zi Xue Xuan; Zi Xue Xuan; Li Chen; et al. (Frontiers in Medicine)
ObjectiveWith the increasing use of fluoroquinolones (FQs) for anti-infective therapy, the adverse events (AEs) caused by their collateral effects pose a key challenge in their clinical application. Hypoglycemia AEs are a type of AE linked to FQs and are commonly observed in real-world settings. Our objective was to provide a comprehensive analysis and summary of hypoglycemia AEs associated with FQs, specifically focusing on moxifloxacin (MOX), ciprofloxacin (CPR), and levofloxacin (LEV).MethodsDisproportionality analysis was used to assess the strength of the association between fluoroquinolone (FQ)-related hypoglycemia and potential safety signals, using data from the Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) covering quarters from 2014 Q1 to 2023 Q4. We utilized Standardized MedDRA Queries (SMQs) at the preferred term (PT) level to retrieve AE data from the FAERS reports. Following the removal of duplicate reports, a disproportionality analysis was conducted to identify potential safety signals associated with FQ-related hypoglycemia by calculating the reporting odds ratio (ROR). In addition, clinical characteristics, onset timing, oral and intravenous administrations, and serious outcomes related to FQ-associated hypoglycemia were further analyzed to provide a comprehensive understanding of the safety profile.ResultsA total of 242,509 AE reports linked to FQs were detected, of which 16,306 indicated hypoglycemia signals. Among these cases, a higher percentage involved female patients than male patients (52.55% vs. 36.07%). The demographic analysis indicated that FQ-induced hypoglycemia was mainly concentrated in patients aged 18 ~ 64 years, with the mean age ranging from 51.14 to 57.39 years. Moreover, CPR had the most cases of hypoglycemia and related conditions (ROR 99.02, PRR 98.15, IC 35.66, EBGM 96.79), while LEV was relatively weakly associated with hypoglycemia (ROR 82.78, PRR 82.45, IC 27.89, EBGM 81.02). This study showed that all three FQs detected positive signals of hypoglycemia within 1 week. Oral fluoroquinolone-induced hypoglycemia had stronger signal strength than intravenous administration. Regarding the mortality and disability rates associated with hypoglycemia, MOX had the most cases of severe adverse drug events.ConclusionFQ-induced hypoglycemia tends to occur early and can have serious consequences. Our preliminary findings provide a better understanding and emphasize the need for enhanced monitoring of potential hypoglycemia linked to FQ treatment.